National reporting codes for the mineral industry: The case of JORC in Australia. - Kalaitzidis, S. (Bulletin of the Geological Society of Greece, 2013)
A revised version of the Australasian Code for Reporting of Exploration Results, Mineral Resources and Ore Reserves commonly called the JORC Code was released in Australia in December 2012. This paper provides a summary of the principles that guide the Code, and the definitions therein, as well as the rationality behind adopting the Code as a Public Reporting tool. Brief examples of reporting requirements are also discussed. Additionally, references and a general comparison to the Pan-European Reserves & Resources Reporting Code (PERC standard) are presented. Although, in Greece there is no relevant Regulatory Framework in place yet or enforcement of any International Code, the adaptation of PERC is probably ahead, and hence this paper aims to open the discussion among geoscientists and mining engineers for the opportunities and the challenges that they will face.